FACTOR INFLUENCING TO HEALTH PROMOTION BEHAVIOR FOR CORONAVIRUS DISEASE 2019 (COVID-19) PREVENTION OF OLDER ADULTS - Bunthan, Winthanyou; Whaikit, Phatcharaporn; Soysang, Viparporn; Soynahk, Chutima; Akaratanapol, Prisana; Kompayak, Jariyawat (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
This research aimed to study factors affecting the health promotion behaviors and Coronavirus disease 2019 (COVID-19) prevention in the elderly. Samples were 122 older people who lived in the 2nd and 3rd year of nursing students, Faculty of Nursing, Huachiew Chalermprakiet University who lives with older person during the Coronavirus disease 2019 (COVID-19) period. Samples were selected by the simple random sampling technique using a nursing student list. The sample size was estimated using G*Power. The data were collected during May 2020. The research instruments were 1) the questionnaire asking general information of respondents, 2) the questionnaire asking factors affecting the health promotion behaviors and Coronavirus disease 2019 (COVID-19) prevention, and 3) the assessment test of the health promotion behaviors and Coronavirus disease 2019 (COVID-19) prevention. All research instruments were validated in terms of content validity by five experts in the field. The reliability of research instruments, considering the Cronbach’s alpha were .843 and .764, respectively. The quantitative data were analyzed using multiple regression. The result found that the elderly had a high level of the health promotion behaviors and Coronavirus disease 2019 (COVID-19) prevention (M=2.18, SD=.50), Perceived benefits of action (Beta=.200, p=.011). The factor perceived barriers to action (Beta= -.189, p=.002), perceived self-efficacy (Beta=.313, p=.000), interpersonal influences (Beta=.193, p=.004), and situational influences (Beta=.212, p=.007) were able to predict the health promotion behaviors and Coronavirus disease 2019 (COVID-19) prevention of the elderly at 61.20 percentages (R2=.612, Adjusted R2=.595, p=.000). Perceived self-efficacy was the greatest factor affecting the health promotion behaviors and Coronavirus disease 2019 (COVID-19) prevention in the elderly (Beta=.313, p=.000).